The failures and possibilities of philosophy in the material world - Van Cleave, Jessica; Marn, Travis; Wolgemuth, Jennifer (International Review of Qualitative Research, 2025)
Keywords: Engineering; Engineering ethics; Epistemology; Philosophy; dept.cur

Manufacturing Trustworthiness in Qualitative Research as a Writerly and Readerly Accomplishment: Introduction to the Special Issue - Van Cleave, Jessica; Wolgemuth, Jennifer; Marn, Travis (Qualitative Inquiry, 2025)
Keywords: Construct (python library); Product (mathematics); Qualitative research; Space (punctuation); Theme (computing); Tinker; Trustworthiness; dept.cur; possibility; publication; scholarly writing; trustworthiness

On the sidelines of what works: scientifically based indifference - Wolgemuth, Jennifer R.; Marn, Travis M.; Sabnis, Sujay (International Journal of Research & Method in Education, 2021)
A team of systematic reviewers successfully completed a government-commissioned review of ‘what works to improve post-school outcomes for youth with disabilities’ in 2012. Despite its success, interviews with 10 review team members revealed dissatisfaction with the process and indifference to its outcomes. The purpose of our analysis was to examine how the systematic review process itself led to review team members’ feelings of indifference, resignation, and pessimism. Drawing on the writings of Henry Giroux, Gert Biesta, and Hanna Arendt that warn of the death of democracy and the rise of totalitarianism, we explored how the systematic review certification process, examinations, rules, and structures deadened democratic deliberation and critique necessary, we argue, to conducting good educational science. We end with a call for systematic reviews in education whose researchers, products, and processes remain ethically oriented to keeping democracy alive. © 2021 Informa UK Limited, trading as Taylor & Francis Group.
2 citations (Crossref) [2023-10-31]
Keywords: dept.cur; peer-reviewed

#scholar #famous #monster - Wolgemuth, Jennifer; Lester, Jessica; Guyotte, Kelly; Koro‐Ljungberg, Mirka; Marn, Travis (Educational Researcher, 2025)
Academic success is now coupled with social media engagement. Social media has become so normalized in the academy that absent a carefully curated social media presence, scholars risk being seen as unscholarly, unproductive, and unpopular. This article lays bare the pressures, mechanisms, and monstrosities of using social media to promote scholarship. We argue that the widespread adoption of social media outpaces critical attention to its ethics and wonder about the future of public scholarship and the monstrous scholarly selves we are becoming. Thinking of monstrosity, with Krecˇicˇ and Žižek, as the preontological domain that rests beneath society and constitutes alterity and otherness, we ask what kinds of #scholarfamousmonsters we want to be, become, and promote in the digital era.
Keywords: Aesthetics; Art; Epistemology; Law; Literature; Media studies; Monster; Philosophy; Political science; Psychology; Scholarship; Social media; Social psychology; Sociology; Wonder; dept.cur; peer-reviewed